Miracles Tradition and a Critique on Hume's Theory - Khanjani, Qasem (Journal of History Culture and Art Research, 2017)
Since appearing miracles and distancing them, denying or doubting Prophets' miracles and miracles tradition has had an old precedent. Although it may be imagined these oppositions have been proposed by the western philosophers and learned, but investigating the ancient sources and the past Islamic philosophers and learned we can find out that opposing these traditions has happened continuously since appearing miracles namely since the Prophets (PBUH). In modern era also some western learned, including David Hume, have embarked upon showing the miracles tradition and consequently the very miracles to be blemished and undocumented. Opposing Hume and answering his objections began during his own life and has been continued up today. In this article Hume's opinion will be studied and considering the experts' opinions in Islamic and Western world his objections will be answered.